Two-dimensional deformation of an elastic layer subjected to surface loads - Rani, Salma; Rani, Sunita (Zielona Góra: Uniwersytet Zielonogórski)
The two-dimensional deformation of a uniform, elastically isotropic layer of a finite thickness (FT) over a rough-rigid base caused by surface loads has been solved analytically. The stresses and the displacements for an isotropic layer are obtained in the integral form by applying the Airy`s stress function approach. Using the appropriate boundary conditions, the problem of surface loads is discussed in detail. The integrals cannot be evaluated analytically due to the complicated expression of denominator.
Keywords: Airy stress function; two-dimensional deformation; least square approximation; rough-rigid base; surface loads